Bioactive Surfaces - Borner, Hans G.; Lutz, Jean-Francois.; Badi, N. (Nezha).; SpringerLink (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
Wischerhoff, Nezha Badi, André Laschewsky and Jean-François Lutz Smart Polymer Surfaces: Concepts and Applications in Biosciences * S. Petersen, M. Gattermayer and M. Biesalski Hold on at the Right Spot: Bioactive Surfaces for the Design of Live-Cell Micropatterns * Julien Polleux Interfacing Cell Surface Receptors to Hybrid Nanopatterned Surfaces: A Molecular Approach for Dissecting the Adhesion Machinery * Abigail Pulsipher and Muhammad N. Yousaf Self-Assembled Monolayers as Dynamic Model Substrates for Cell Biology * D. Volodkin, A. Skirtach and H. Möhwald LbL Films as Reservoirs for Bioactive Molecules * R. Gentsch and H. G. Börner Designing Three-Dimensional Materials at the Interface to Biology *   Joerg C. Tiller Antimicrobial Surfaces
H.G. Börner and J.-F. Lutz : Introduction -- J.-F. Lutz and A. Laschewsky: Smart Polymer Surfaces -- M. Biesalski: Peptide, Protein and Bioconjugate Decorated Surfaces -- M. Yousaf: SAMS and Dynamic Surfaces -- D. Volodkin and H. Möhwald: LbL Films as Reservoirs for Bioactive Molecules -- H. G. Börner and R. Gensch: 3D-Surfaces and Scaffolds in Biocontact -- J. Tiller: Antimicrobial Surfaces -- D. Discher: Control of Stem-Cell Growth -- H.G. Börner and J.-F. Lutz: Perspectives.-.
Electronic reproduction.
Keywords: Biological interfaces; Polymers -- Surfaces